Advancing the management of obstructive airways diseases through translational research. Issue 5 (13th March 2018) - Porsbjerg, C.; Sverrild, A.; Baines, K. J.; Searles, A.; Maltby, S.; Foster, P. S.; Brightling, C.; Gibson, P. G.
Summary: Obstructive airways diseases (OAD) represent a huge burden of illness world‐wide, and in spite of the development of effective therapies, significant morbidity and mortality related to asthma and COPD still remains. Over the past decade, our understanding of OAD has improved vastly, and novel treatments have evolved. This evolution is the result of successful translational research, which has connected clinical presentations of OAD and underlying disease mechanisms, thereby enabling the development of targeted treatments. The next challenge of translational research will be to position these novel treatments for OAD for optimal clinical use. At the same time, there is great potential in these treatments providing even better insights into disease mechanisms in OAD by studying the effects of blocking individual immunological pathways. To optimize this potential, there is a need to ensure that translational aspects are added to randomized clinical trials, as well as real‐world studies, but also to use other trial designs such as platform studies, which allow for simultaneous assessment of different interventions. Furthermore, demonstrating clinical impact, that is research translation, is an increasingly important component of successful translational research. This review outlines concepts of translational research, exemplifying how translational research has moved management of obstructive airways diseases into the next century, with the introduction of targeted, individualized therapy. Furthermore, the review describes how these therapies may be used as research tools to further our understanding of disease mechanisms in OAD, through translational, mechanistic studies. We underline the current need for implementing basic immunological concepts into clinical care in order to optimize the use of novel targeted treatments and to further the clinical understanding of disease mechanisms. Finally, potential barriers to adoption of novel targeted therapies into routine practice and how these may be overcome are described.